2019
DOI: 10.21037/atm.2019.05.45
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to prevent stricture after esophageal endoscopic submucosal dissection

Abstract: Endoscopic submucosal dissection (ESD) has been widely applied as a less invasive and more effective method for treating early esophageal cancers such as squamous cell carcinoma and dysplasia of Barrett's esophagus. However, post-ESD esophageal stricture often occurs if patients suffer circumferential mucosal defects of more than three-quarters of the circumference of the esophagus, which makes it difficult for patients to swallow and greatly reduces their quality of life. Moreover, there is currently no stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…These histological findings suggest that locoregional TA injection suppresses the proliferation of the SF and may contribute to the prevention of esophageal strictures after widespread ESD. Previous studies have reported methods, such as preventive balloon dilatation, steroid administration, esophageal stent treatment, and tissue engineering, to prevent post-ESD esophageal stricture [11,[17][18][19][20][21][22]. Among these methods, steroid administration to prevent stricture included oral steroid administration, TA injection, and TA-filling method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These histological findings suggest that locoregional TA injection suppresses the proliferation of the SF and may contribute to the prevention of esophageal strictures after widespread ESD. Previous studies have reported methods, such as preventive balloon dilatation, steroid administration, esophageal stent treatment, and tissue engineering, to prevent post-ESD esophageal stricture [11,[17][18][19][20][21][22]. Among these methods, steroid administration to prevent stricture included oral steroid administration, TA injection, and TA-filling method.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported methods, such as preventive balloon dilatation, steroid administration, esophageal stent treatment, and tissue engineering, to prevent post-ESD esophageal stricture [ 11 , 17 22 ]. Among these methods, steroid administration to prevent stricture included oral steroid administration, TA injection, and TA-filling method.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al. [ 45 ] classified strategies to prevent esophageal stricture after ESD into five categories: (1) Pharmacological prophylaxis, (2) Mechanical strategies, (3) Tissue engineering strategies, (4) Autologous transplantation, and (5) Other novel strategies. Cell sheets transplantation and extracellular matrix approaches are included in the Tissue engineering strategies.…”
Section: Evaluation Of Regenerative Therapy By Endoscopic Transplantamentioning
confidence: 99%
“…Endoscopic submucosal dissection (ESD) is the standard treatment for early esophageal cancer with minimal or absent risk of lymph node metastasis [1][2][3]. Unfortunately, resections comprising more than 70-80 % of the circumference are associated with a high risk (up to 100 %) of stricture formation [4,5]. To date, steroidseither applied by repetitive local injection [6,7] or as systemic high dose treatmentare most often used to prevent strictures [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, resections comprising more than 70-80 % of the circumference are associated with a high risk (up to 100 %) of stricture formation [4,5]. To date, steroidseither applied by repetitive local injection [6,7] or as systemic high dose treatmentare most often used to prevent strictures [4,8,9]. However, even the use of such preventive measures does not completely avoid strictures that require endoscopic treatment.…”
Section: Introductionmentioning
confidence: 99%